2014
DOI: 10.7150/ijbs.9518
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin, a Novel Versatile Player Regulating Energy Metabolism beyond the Erythroid System

Abstract: Erythropoietin (EPO), the required cytokine for promoting the proliferation and differentiation of erythroid cells to stimulate erythropoiesis, has been reported to act as a pleiotropic cytokine beyond hematopoietic system. The various activities of EPO are determined by the widespread distribution of its cell surface EPO receptor (EpoR) in multiple tissues including endothelial, neural, myoblasts, adipocytes and other cell types. EPO activity has been linked to angiogenesis, neuroprotection, cardioprotection,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
82
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 231 publications
(314 reference statements)
2
82
1
1
Order By: Relevance
“…Initial blood glucose levels may thus be critical in the acute effect of EPO, consistent with the study reporting that hyperglycemia is necessary for stimulation of EPO-induced glucose uptake in adipocytes (Mikolás et al 2012). As we have also shown that rat soleus muscle did not express EPOR, AKT activation in our model is likely to be indirect via a still unknown mechanism (Wang et al 2014). In human, acute i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Initial blood glucose levels may thus be critical in the acute effect of EPO, consistent with the study reporting that hyperglycemia is necessary for stimulation of EPO-induced glucose uptake in adipocytes (Mikolás et al 2012). As we have also shown that rat soleus muscle did not express EPOR, AKT activation in our model is likely to be indirect via a still unknown mechanism (Wang et al 2014). In human, acute i.v.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 In addition to endocrine stimulation of erythropoiesis, EPO promotes endothelial cell survival and proliferation in vitro and in vivo. 9,10 Like VEGF tub mice, Epo transgenic mice develop hematocrit of approximately 80%, have normal BP and renal function, and have no evidence of cardiovascular disease or thrombotic events. This remarkable adaptation was found to be mediated by increased endothelial NOS (eNOS) expression and nitric oxide (NO) levels.…”
mentioning
confidence: 99%
“…Erythropoietin exerts multiple effects in different organs and tissues (Wang et al, 2014). In hematopoietic tissues, EPO is involved in the cell cycle progression, proliferation, and differentiation of erythroid progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies on EPO-R showed that this receptor is only expressed in cells of the erythroid lineage, emphasizing that the action of EPO is limited to red blood cell manufacturing, while further studies divulged the wide expression of the EPO-R, increasing the likelihood of extra-hematopoietic effect of EPO (Wang et al, 2014). The detection of EPO-R mRNA in the brain, heart, retinal, skeletal, muscle, and kidney cells makes it a promising target to study its untold functions (Morishita et al, 1997;Wu et al, 1999;Noguchi et al, 2008;Hu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%